Experiência de participação em atividades comunitárias: o olhar do jovem - Corrêa, Julia Shellard (2013)
This research aimed to investigate how young people understand their experience of participation in community activities. More specifically, to understand how this activity was shaping up in the life Young. The concept of participation was based on Paulo Freire s work. He understand that man is an incomplete being in search of his humanization, which occurs due to the relationships within others and his social and cultural reality. Participation is the presence and involvement of youth in this search for humanize. The method consisted of two individual reflexive interviews, with young people of a community in the north of São Paulo. These young people were nominated by the community leadership as participants in local activities. From groups of interviewees' statements, a discussion relating them to the theory that underlies this study was made. There were different understandings of participation in interviews, as help and collaboration, ranging between the extremes of 'false' and 'true' participation, as defined by Paulo Freire. Regarding their history of participation, reference were made to the use and occupation of community spaces, highlighting the experience of being seen as responsible for cultural and historical reality transformation in their community, during childhood and adolescence. From these reports, it was concluded that participate in community activities is part of a history and a community participation experiences